Changing prices... changing times: evidence for Italy - Mario Porqueddu; Silvia Fabiani (European Central Bank (ECB), 2017)
This paper examines the process of adjustment of prices in Italy to determine whether nominal flexibility, measured by the frequency of price changes, has increased in the recent years of protracted stagnation and double-dip recession. The analysis is based on a large micro-level dataset of individual prices collected monthly by Istat from 2006 to 2013 for the Consumer Price Index. We find that both the percentage of prices adjusted monthly and the average size of the adjustment have risen significantly since the 1996-2001 period, in particular for downward changes. This greater flexibility is related in part to the spread of modern distribution structures. Our estimates further indicate that the recession has affected the price adjustment mechanism: for manufactures, price cuts have become larger and more frequent, while increases are more moderate; for services, both the frequency and the size of price increases have diminished.
Keywords: E31; D21; D40; L11; 330; consumer prices; frequency of price adjustment; nominal flexibility